Extent of Knowledge of Fish farmers about Scientific Fish Culture Practices in North 24 Parganas of West Bengal, India (Indian Journal of Extension Education, 2017)
The study was conducted in North 24 Parganas district of West Bengal. It was found that majority of the fish farmers (50.8%) had the medium level of knowledge regarding scientific fish culture practices. The highest extent of knowledge was observed in the names of some aquatic weeds (95.83%), and lowest was observed in the minimum depth of water required for fish culture and the time gap required between manure application and stocking of fish seed (26.67%). The path analysis indicated that innovative proneness was the most potent variable in effecting the knowledge of fish farmers positively.